Step into the metaverse : how the immersive internet will unlock a trillion-dollar social economy - Van Rijmenam, Mark (John Wiley & Sons, Inc., 2022)
An incisive glimpse into the future of the internet In Step into the Metaverse: How the Immersive Internet Will Unlock a Trillion-Dollar Social Economy, future tech strategist, entrepreneur, and thought leader Dr. Mark van Rijmenam delivers a startlingly insightful discussion about how the world as we know it will fundamentally change as the physical and the digital worlds merge into the metaverse, impacting the everyday experiences of people, companies, and societies. The author maps out the extraordinary opportunities and challenges facing business leaders, consumers, regulators, policymakers, and other metaverse stakeholders trying to navigate the future of the Internet. In the metaverse, you can be who you want to be, where you want to be, and companies and consumers are only restricted by their own creativity how they can benefit from the immersive internet. With engaging commentary on issues ranging from avatars, identity and digital fashion to non-fungible tokens (NFTs), blockchain and the economics of the metaverse, this book also offers: Discussions on the importance of an open and interoperable metaverse build on the web 3.0 paradigm if we want to reign in the control of Big Tech over our identity, data and lives. Explorations of the enormous--and largely untapped--potential for metaverse entertainment, including gaming, music, media, and sports and how brands can engage with their customers in novel ways and how digital twins will change how we work and innovate. Considerations related to the dangers of an always-on, immersive internet, including data breaches, avatar imposters, mental health issues, corporate and state surveillance, and the need for metaverse law. A fascinating read you won't be able to put down, Step into the Metaverse belongs in the hands of executives, managers, and other business leaders who play a role in digital transformation or execution. It's also an invaluable resource for anyone interested in the future of technology, the internet, and social interaction.